The fundamental right to the information and transparency in the anticorruption law: Is it going forward or backward? - Friedrich, Denise Bittencourt; Sbardelotto, Fábio Roque (Revista do Direito, 2016)
The question which motivated this work refers to the fact whether the rules anticorruption law (Law 12.846/13) and its respective decree represents a step forward or backward with the scope of information and transparency of companies that contract with the government. This approach has its origin in the necessity of thinking ways to ensure the ethics in government procurements, especially in the private sector, which is part the contractual legal relationship. The method used in this work is the hypothetical-deductive method due the presented problem, there is a chance that the republican values entered in the constitution, the effectiveness of the rights and duties to information goes through an effort to extend it to a private initiative in contracts with the government, given the public interest involved, and from this point, it will be promoting the principle of public morality. To answer this question, it was used the analysis of the anticorruption law, given such concern for the ethical management of the companies that contract with the government. However, the scope of this work is to investigate how this legal tool as well as the decree that regulated it treated the transparency questions related with the managements of such companies. It was noticed that the corruption regulation directed to the private sector is a great step forward, but it cannot be taken as a conclusion of this work. The treatment given by the anticorruption law was lacked, the situation that it was remained in its regulated decree has backwards points.